Experimental model to assess the Tritrichomonas foetus vaccine- induced effects - Soto, P. (2018)
The purpose of this work was to present an experimental murine model as an alternative to the bovine one, to evaluate the efficacy of experimental vaccines against Tritrichomonas foetus. The vaccines employed consisted of inactivated protozoa with different formulations: (A) with oil adjuvant, (B) aqueous vaccine, (C) aqueous vaccine with dimethyl sulphoside. Seventy female BALB/c mice were used and distributed in 7 experimental groups; each group received 2 doses of vaccine, two groups received a vaginal booster at the time of the second dose. Fifteen days after the second dose, all animals were challenged by vaginal instillation with T. fetus. Blood samples and vaginal mucus were taken until day 30 post infection. The immune response was evaluated by ELISA and the vaginal infection assessed by vaginal mucus culture in the TYM medium. The greatest immune response was related to a lower number of infected animals post challenge and a rapid elimination of the protozoa of the reproductive tract. These results allow us to present an alternative experimental model and inexpensive to evaluate power test of current commercial vaccines and new developments of immunogens against bovine trichomonosis.